Carbon reinforced carbon fibers: Using surface modification as a route to enhanced physical performance. (8th February 2022) - Dharmasiri, Bhagya; Randall, James; Yin, Yanting; Andersson, Gunther G.; Doeven, Egan H.; Francis, Paul S.; Henderson, Luke C.
Abstract: In this work, a conductive polymer of ortho -phenylenediamine ( o -PD) is grown on the surface of carbon fibers that structurally resembles cyclized poly(acrylonitrile) (PAN) formed during the traditional carbon fiber manufacturing process. The surface modification was conducted using electrical potential cycling (−1 V to +1 V vs Ag/AgCl) and the physical properties of the treated fibers improved significantly. Tensile strength increased by 44.9% relative to control fibers (4.58 ± 0.06 GPa from 3.16 ± 0.05 GPa), while tensile modulus increased from 239.6 ± 0.9 GPa to 276.4 ± 1.1 GPa, for the treated and control fibers, respectively. Interfacial adhesion in epoxy resin was improved by 189%, relative to control fibers. Exposing these modified fibers to high temperatures used in the carbonization of PAN (1400 °C) encouraged the carbonization of the surface bound polymer, similar to that seen in the conversion of oxidized PAN to carbon fiber on a continuous scale. The improved physical properties from the initial modification were largely retained, and the thermal stability of the modified fibers in air is improved significantly without compromising the interfacial adhesion of the original unmodified fibers. Graphical abstract: Image 1